Miten muuttuu runokylien kieli:reaaliaikatutkimus jälkitavujen A-loppuisten vokaalijonojen variaatiosta vienalaismurteissa - Kunnas, N. (Niina) (University of Oulu, 2007)
Abstract In my research I look at sound structure variation and change in the Viena dialect of two Karelian villages Jyskyjärvi and Kalevala. I explore how the final syllable A-ending vowel combinations (iA, eA, UA and OA) and long vowels aa and ää are represented in modern Viena dialects and how vowel clusters have changed in pronunciation over a period of thirty years. I study the change in language in real-time: I compare recorded interviews made between 1967–1971 and 2001. Methodologically my research stems from the sociolinguistic research tradition as well as language contact research. The central question is how the closely related Finnish language has perhaps begun to affect the Viena Karelian language. Looking at linguistic changes, one aim is to test morphological and lexical diffusion theories and strive to advance said theories. As regards idiolectic variation, I explore how the language attitudes of the informants affect their language variation and how a social network and its structure can explain the differences in idiolectic variation. The results show that there is a significant amount of variation in Viena Karelian’s final syllable A-ending vowel clusters. This may have been affected by the minority position and endangered status of the Karelian language as well as the great changes in the society. Variation and linguistic change is affected by, among other things, morphological factors, frequency of lexemes, and the attempt at symmetry of the vowel clusters. In certain vowel clusters the typical variant of Viena dialects has become more common. However, in certain vowel clusters, a contact-initiated variant has increased in popularity. The data also show changes, which seem to have been affected by reasons external to the language (language contact) and reasons internal to the language (emergent systemic change). In this study, the testing of the diffusion theories shows that contact-initiated variants are becoming more common often in the order of an inverted morphotactic hierarchy and more ...